2009
DOI: 10.1002/pnp.113
|View full text |Cite
|
Sign up to set email alerts
|

Management of depression during pregnancy

Abstract: In Pregnancy is a series of reviews focusing on the management of women with psychiatric and neurological conditions during pregnancy. In this article, Dr Osborne and Dr O'Keane discuss the risks discuss the risk factors for the development of depression during pregnancy, its possible impact on the developing foetus and the current recommended management. Copyright © 2009 Wiley Interface Ltd

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Depression experienced during pregnancy may persist until post birth if it is not treated well since pregnancy [12]. It can lead to negative impact of the fetus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depression experienced during pregnancy may persist until post birth if it is not treated well since pregnancy [12]. It can lead to negative impact of the fetus.…”
Section: Introductionmentioning
confidence: 99%
“…Previous study conducted by Deave, Heron, Evans, and Emond [9] found that depression during pregnancy can cause development delay of children. Depression that continues post birth process can disrupt the process of adaptation of mother and child, and negatively impact on attachment and infant care of mother to child [12].…”
Section: Introductionmentioning
confidence: 99%